Development and characterization of sulfonated olyethersulfone membrane as a potential material for direct methanol fuel cell - Rosmainiza, Ibrahimi Husaimi (2008)
Sulfonated polyethersulfone membrane is one of the potential candidates to be use as an electrolyte for fuel cell application due to its high thermal resistance. With a high heat deflection temperature of 400°F (204°C), it can withstand continuous exposure to heat and still absorb tremendous impact without cracking or breaking. Sulfonated polyethersulfone membrane has been prepared by conducting sulfonation process with sulfuric acid as a sulfonating agent and then the polymer precipitated had been dissolved in N-Methyl-2-pyrrolidone. The functional groups of sulfonic acids have been successfully incorporated in the PES backbone and detected using FTIR at 1033cm -1 wavelength. Membranes with 35.7% degree of sulfonation possess water uptake at the room temperature of 13.1 wt% and the value of IEC is about 11.43 mmol/g. The water uptake of the sulfonated polyethersulfone membrane increased with temperature from 13.1 wt% up to 46 wt%. Meanwhile, the methanol uptake was increased with an increased in concentration from 14.9 wt% to 26.2 wt%. Membranes prepared from SPES showed lower decomposition temperature and have good properties to be applied as a membrane for DMFC.